Facade, Hindustan Bhavan - Ghosh, Ayan (2023)
Hindustan Bhavan on S Vallabhdas Road is named after Hindustan Petroleum Ltd., the owner of the building. The entrance porch is supported by two sets of twin pillars. The windows at the upper levels have weather shades supported on brackets. The first-floor windows have projecting balconies supported by a cornice that runs around the building.